Effects Of The Covid-19 Pandemic On The Trends Of Pregnant Mother Anxiety Disorders In South Kalimantan In 2021 - Zaiyidah Fathony; Rizki Amalia; Pratiwi Puji Lestari (MBUnivPress, 2021)
The COVID-19 pandemic has had an impact on all aspects of life. The Covid-19 pandemic is not only threatening people's health physically, but also mentally. Mental health is one of the impacts that threaten society during the Covid-19 pandemic. Mental health issues are increasingly being recognized as a significant and worrying secondary effect of the COVID-19 pandemic. This study aims to determine the effect of the COVID-19 pandemic on mental health, in this case the tendency for anxiety disorders of pregnant women in South Kalimantan. This research is an observational study. The sample was taken by total sampling from data on pregnant women recorded at the South Kalimantan Provincial Health Office. The COVID-19 pandemic did not have a statistically significant effect on the tendency of anxiety disorders. Of the 3 variables studied, namely age, education and occupation, there was no significant relationship between anxiety disorders in pregnant women during the COVID-19 pandemic